Comparing subspecialty and intensive care providers perspectives on pediatric complex chronic patients: A survey study. (September 2021) - Kobussen, Taylor A; Hansen, Gregory; Holt, Tanya R
Introduction: Pediatric complex chronic care patients present unique challenges regarding healthcare provision: complex medical regimes, complicated family/provider dynamics, and multiple healthcare teams that can result in inconsistent care. This study examined subspecialty providers' perspectives regarding pediatric complex chronic care patients and compared them with acute care providers while exploring opportunities to better facilitate care provided to pediatric complex chronic care patients. Methods: This survey study occurring within a Canadian tertiary care pediatric center, utilized REDCap to deploy surveys involving Likert Scale and short answer questions. The Kruskal–Wallis test compared subspecialty provider perspectives when providing care to pediatric complex chronic care patients versus non-pediatric complex chronic care patients; and perspectives between subspecialty and acute care providers. Results: Survey response rate was 24/46 (52.2%). Eight overarching themes emerged from Likert scale questions. Short answer questions revealed factors that may facilitate care provided to pediatric complex chronic care patients: access to funding; discharge planning; communication methods between specialists; and healthcare provider continuity. Several differences were identified when working with pediatric complex chronic care patients, compared to non-pediatric complex chronic care patients: increased time/resource burden; managing expectations of patients/families; navigating discrepancies in goals of care; complexity of coordination between services; increased efforts in coordinating discharge from hospital and working with medicalized patients/families. Discussion: Exploring pediatric subspecialty provider perspectives of pediatric complex chronic care patients revealed opportunities to enhance care provided: increased resources to ease the strain of care provision for parents, implementation of a discharge coordinator, complex care clinics with a pediatrician to "quarterback" care, and co-management between the complex care pediatrician and acute care physician when admitted to an acute care service. Implementation of these initiatives may improve the care provided to pediatric complex chronic care patients.